[tex]a) \ -3\frac{1}{2}-(-1\frac{1}{3}) = -3\frac{3}{6}+1\frac{2}{6} = -2\frac{1}{6}\\\\b) \ -2,15 - 1,9 = -4,05\\\\c) \ 3\frac{7}{8}-(-1,5) = 3,875+1,5 = 5,375[/tex]
2.
[tex]a + (-3\frac{5}{6})=-2,8\\\\a = -\frac{28}{10}+\frac{23}{6}\\\\a = -\frac{14}{5}+\frac{23}{6}\\\\a = -\frac{84}{30}+\frac{115}{30}\\\\a = \frac{31}{30} = 1\frac{1}{30}\\\\\\Spr.\\\\L = \frac{31}{30}+(-3\frac{5}{6}) =\frac{31}{30}-\frac{23}{6} = \frac{31}{30}-\frac{115}{30} = -\frac{84}{30}\\\\P = -2,8 = -\frac{28}{10} = -\frac{84}{30}\\\\L = P[/tex]